2015
DOI: 10.19081/jpsl.5.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Mangrove Rehabilitation using Guludan Technique in Carbon Trade Perspective in Protected Mangrove Area in Muara Angke, DKI Jakarta Province

Abstract: Mitigation of climate change due to CO2 emissions, the forestry sector developed a REDD+ scheme. This study was conducted to examine financial feasibility of the mangrove rehabilitation with guludan technique, so that further funding of mangrove rehabilitation can be included into REDD+ scheme. Guludan technology was developed to overcome the deep water column for mangrove rehabilitation in the former pond area. This technique has been developed for mangrove species Avicennia marina with spacing 0.25 m x 0.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…The survival of mangroves planted in the horizontal aquaponic system is presented in Table 5. Horizontal aquaponic is an alternative for mangrove rehabilitation in inundated areas other than gulud system (Yanuartanti et al 2015) and vertical aquaponic method. This method is much cheaper than the two rehabilitation techniques.…”
Section: The Survival Rate Of Mangroves Planted In the Horizontal Aqu...mentioning
confidence: 99%
See 4 more Smart Citations
“…The survival of mangroves planted in the horizontal aquaponic system is presented in Table 5. Horizontal aquaponic is an alternative for mangrove rehabilitation in inundated areas other than gulud system (Yanuartanti et al 2015) and vertical aquaponic method. This method is much cheaper than the two rehabilitation techniques.…”
Section: The Survival Rate Of Mangroves Planted In the Horizontal Aqu...mentioning
confidence: 99%
“…The data also showed that Rhizophora spp. and A. marina had the best survival rate when planted in the horizontal aquaponic system due to its unique and good adaptation ability in reducing the impact of high and permanent water inundation (Hilmi et al 2021a;Yanuartanti et al 2015).…”
Section: The Survival Rate Of Mangroves Planted In the Horizontal Aqu...mentioning
confidence: 99%
See 3 more Smart Citations